Analyzing Greenwashing Impact on Financial Performance and Profitability of Publicly Listed Manufacturing Companies in Makassar - Istianah Hadaming; Wa Ode Rayyani (Penerbit Goodwood, 2026)
Purpose: This study empirically tests the effect of greenwashing practices on the financial performance of publicly listed manufacturing companies operating in Makassar between 2021 and 2025, using Return on Assets as the profitability proxy. Methodology: A quantitative approach was applied using secondary data drawn from annual reports and sustainability reports. Simple linear regression together with a content analysis method was used to score the level of greenwashing for each company-year observation.Results: The relationship between greenwashing and Return on Assets was negative but not statistically significant, with a regression coefficient of negative 0.008 and a significance value of 0.911, while the model explained only 0.1% of the variance in profitability.Conclusions: The negative direction confirms that symbolic environmental claims made without matching action tend to create operational inefficiency that weighs on profit, although the regional capital market remains pragmatic and continues to value traditional financial metrics above sustainability narratives.Limitations: The study is confined to a small sample of manufacturers with operations in the Makassar industrial area and relies solely on Return on Assets as the financial performance proxy. Contribution: The study offers empirical evidence on greenwashing dynamics at the regional operational level, highlighting the gap between centralized corporate narratives and local realization, and points toward the need for stronger regional sustainability verification mechanisms.